Theological-political treatise - Spinoza, Benedictus de, 1632-1677; Israel, Jonathan I. (Jonathan Irvine), 1946-; Silverthorne, Michael (Cambridge : Cambridge University Press, 2007)
Spinoza's Theological-Political Treatise (1670) is one of the most important philosophical works of the early modern period. In it Spinoza discusses at length the historical circumstances of the composition and transmission of the Bible, demonstrating the fallibility of both its authors and its interpreters. He argues that free enquiry is not only consistent with the security and prosperity of a state but actually essential to them, and that such freedom flourishes best in a democratic and republican state in which individuals are left free while religious organizations are subordinated to the secular power. His Treatise has profoundly influenced the subsequent history of political thought, Enlightenment 'clandestine' or radical philosophy, Bible hermeneutics, and textual criticism more generally. It is presented here in a translation of great clarity and accuracy by Michael Silverthorne and Jonathan Israel, with a substantial historical and philosophical introduction by Jonathan Israel.
Introduction -- Chronology -- Further reading -- Note on the text and translation -- Theological-Political Treatise. Preface ; On prophecy ; On the prophets ; On the vocation of the Hebrews, and whether the prophetic gift was peculiar to them ; On the divine law ; On the reason why ceremonies were instituted, and on belief in the historical narratives, i.e. for what reason and for whom such belief is necessary ; On miracles ; On the interpretation of Scripture ; In which it is shown that the Pentateuch and the books of Joshua, Judges, Ruth, Samuel and Kings were not written by the persons after whom they are named. The question is then asked whether they were written by several authors or by one, and who they were ; Further queries about the same books, namely, whether Ezra made a definitive version of them, and whether the marginal notes found in the Hebrew MSS are variant readings ; Where the remaining books of the Old Testament are examined in the same manner as the earlier ones ; Where it is asked whether the Apostles wrote their Epistles as apostles and prophets or as teachers, and the role of an Apostle is explained ; On the true original text of the divine law, and why Holy Scripture is so called, and why it is called the word of God, and a demonstration that, in so far as it contains the word of God, it has come down to us uncorrupted ; Where it is shown that the teachings of Scripture are very simple, and aim only to promote obedience, and tell us nothing about the divine nature beyond what men may emulate by a certain manner of life ; What faith is, who the faithful are, the foundations of faith defined, and faith definitively distinguished from philosophy ; Where it is shown that theology is not subordinate to reason nor reason to theology, and why it is we are persuaded of the authority of Holy Scripture ; On the foundations of the state, on the natural and civil right of each person, and on the authority of sovereign powers ; Where it is shown that n
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Philosophy and religion -- Early works to 1800.; Free thought -- Early works to 1800.; Political science -- Early works to 1800.